Conservation Laws by using the Multiplier Method for a Fifth-Order Kdv Equation with Time-Dependent Coefficients and Linear Damping - Bruzòn, M.S.; Gandarias, M.L.; Rosa, R. de la (Journal of Applied Nonlinear Dynamics, 2026)
In this paper we consider a family of fifth-order Korteweg-de Vries equations with time-dependent coefficients and linear damping term. By using the multiplier method of Anco and Bluman we determine all the low order conservation laws.